How organizations respond to crisis: five case studies from the COVID-19 pandemic - Sprandel, Heather (Henry Stewart Talks, 2020)
COVID19, Workforce protection, Supply-chain stabilization, Organizational behaviour, Customer engagement, Financial Stress Testing, Nerve-center integration